Analysis of Climate Change Induced Parameters of South-Eastern Coastal Islands of Bangladesh: Comparison from 1977 to 2017 - Prabal Barua; Syed Hafizur Rahman; Morshed Hossan Molla (Pandawa Institute, 2022)
Climate change is one of the biggest threats for the new millennium, and Bangladesh is considered as